Analysis of integrated antenatal care implementation in Tanggamus district - Inani Inani; Atikah Adyas; Febria Listina; Endang Budiarti; Sugeng Eko Irianto (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Antenatal care (ANC) as one of the early prevention efforts for pregnancy risk factors. The success of the maternal health program can be assessed through the main indikator maternal mortality rate (MMR). MMR is all deaths within the scope of every 100.000 live births. In 2021 there were 7,389 death in Indonesia. Health services for pregnant women or antenatal care must meet a minimum frequency of six prenatal checks and two visits by a doctor. In order for the implementation of the MCH program to run smoothly, aspects of improving the quality of MCH program services are still expected to become priority activities at the district/ City level. Improving the quality of the  MCH Program is also assessed from the size of the program coverage in each work area.Purpose: To analysis of the implementation of an integrated antenatal service program in the Tanggamus Regency Area.Method: This type of research uses qualitative studies. This research was carried out in the Tanggamus Regency Region in March-April 2022. The data collection technique used in this study was a focus group discussion with the coordinating midwife and implementing midwife.Results: Based on integrated antenatal program planning, there are constraints related to human resources, which are still lacking in limited funds, and out of 6 health centers, there are five health centers that do not yet have pregnancy check-up facilities using ultrasound, based on the organization of integrated antenatal programs, due to a shortage of midwives so that the performance of midwives is still there concurrent positions where the midwife is also in charge of the laboratory. Judging from the implementation of the integrated antenatal program, a small portion or as many as 2 Community Health Centers had no problems in antenatal examinations, but most or 4 Community Health Centers implementing integrated antenatal activities did not comply with the guidelines because they did not have an ultrasound device and based on the supervision of the integrated antenatal program the results of activities were recorded. Integrated antenatal care by midwives given the task and authority in the recording.Conclusion: Based planning an integrated antenatal program, there are constraints related to human resources, which are still lacking limited funds; based on implementing an integrated antenatal program, a small part or as many as 2 Community Health Centers, there are no obstacles in antenatal examinations, based on monitoring  integrated antenatal program the results of integrated antenatal activities are recorded by midwives who are given the task and authority in the recording.